Complications after intraoral vertical ramus osteotomy: relationship to the shape of the osteotomy line. Issue 2 (February 2016) - Kawase-Koga, Y.; Mori, Y.; Fujii, Y.; Kanno, Y.; Chikazu, D.; Susami, T.; Takato, T.
Abstract: Intraoral vertical ramus osteotomy (IVRO) is used widely to correct mandibular prognathism. However, several disadvantages of this procedure have been reported, such as condylar luxation and bony interference at the osteotomy site. The aim of this study was to survey the incidence of complications (condylar luxation and bony interference) based on the shape of the osteotomy line. One hundred and eighty-five rami in 118 patients with jaw deformities, which were treated with IVRO, were examined retrospectively. The shape of the osteotomy line and the postoperative complications were examined on panoramic radiographs. Osteotomy lines were classified into three types: vertical, C-shaped, and oblique. Of the 185 osteotomy sites, 98 were vertical, 37 C-shaped, and 50 oblique. Condylar luxation was found in six rami (3.2%); four had undergone vertical osteotomy and two had undergone C-shaped osteotomy. Bony interference occurred in seven rami (3.8%), all with vertical type osteotomy lines. Most complications occurred in the vertical type cases and no complications were found in oblique type cases. Condylar luxation was found mainly in unilateral IVRO cases and bony interference was found in bilateral IVRO cases. These results suggest that the oblique type of osteotomy line has the advantage of avoiding complications.